Photovoice: Young children online English language learning, parents’ voices and its implication to educational policy and provision - Nugroho, Kurniawan Yudhi; Sakhiyya, Zulfa (Indonesian Journal of Applied Linguistics, 2022)
The COVID-19 pandemic has brought significant changes to the education sector. The shift from classroom-based conventional learning to virtual mode means that the study from home policy appears to place responsibilities of students learning on parents. By focusing on primary level education, we explored parents’ voices and aspirations in assisting their children in taking online English language classes. As most of the parents have been overwhelmed, we offer some insights regarding how to mitigate the problems. Using photovoice, fifteen parents whose children were learning English language in primary schools were invited to take the photographs from the online English language learning (OELL) program and discussed the photographs. We used Photovoice in the project to capture parents’ concerns over the program and their relationship with the pandemic. Thematic analysis was used as a tool to generate important themes from the photovoice data. While appreciating the program, our respondents highlighted the obstacles and concerns over the online English learning through their photographs. In this article, we demonstrated, that photovoice not only offered a space to explore parents’ experiences in engaging in their children’s OELL program, but also served as a space for parents’ aspirations in disrupting and influencing educational programs and reforms.